High molecular weight proanthocyanidins: extraction with eutectic solvents from grape pomace and its applications - Neto, Rodrigo de Sousa Trêpa Alves (2022)
Proanthocyanidins (PACs) are polymeric phenolic compounds composed by catechin and its derivatives that are normally obtained from dedicated crops such as quebracho (Schinopsis balansae) and used in the production of leather, wood agglomerates and wine maturation. The most commonly employed PAC’s extractions methods are characterized by the low specificity and efficiency which limits their use in conventional and novel applications with added value. Therefore, the development of innovative extraction methods based on more sustainable biomass sources becomes imperative. Eutectic solvents (ESs) are normally described as being composed of a pair of compounds, a hydrogen bond donor and a hydrogen bond acceptor, have been proposed as a viable alternative to conventional solvents and are one of the most promising solutions in the improvement of extraction processes based on conventional organic solvents. This is due to their low-cost, easiness of preparation, biocompatibility and ability of being tailor-made to a specific application. Within the circular economy concept there has been a growing interest in the use of agroforestry by-products as biomass source for the production of added value compounds and PACs are no exception. Among the available options, grape pomace, a by-product from the wine industry, is one of the most relevant by-products for the obtention of PAC rich extracts due to the high annual production at a global scale, and specifically in Portugal, and because of the high contents of PACs in these byproducts. Hence, the main objective of this thesis is the improvement of the PAC’s extraction from grape by-product using ESs aiming at obtaining fractions with increased purity and with well-defined properties, as well as to explore PAC’s utilization in added value applications. A large part of the information presented here is focused on the study of the effect of ESs different combinations in PACs extraction from grape pomace. In this context, the processes of simple maceration or in combination with microwave irradiation induced heating were optimized by response surface methodology (RSM). Relatively to the simple maceration process it was concluded that the best results were obtained with a quaternary ES system based on choline chloride, glycerol, ethanol and water (mass fractions of 0.5, 0.0, 0.2 e 0.3, respectively) from which was possible to obtain an extraction yield of 126 mgPAC/gBM (mean degree of polymerization (mDP)=6.5). The best results for microwave-assisted extraction were obtained with a ternary ES system based on choline chloride, lactic acid and water (mass fractions of 0.36, 0.39 e 0.25, respectively). In this situation, the extraction time was considerably shorter when compared with the simple maceration process (3.56 min instead of 1h) and the extraction yield was 135 mgPAC/gBM (mDP=7.2). Lastly, the optimized simple maceration system was used in the normalization of extracts obtained from different sources from which was possible to obtain extracts with specific characteristics, namely, mDP values of 6.5 or 7.5, using for that purpose specific solvent compositions for each grape pomace and mDP value. Finally, some PACs’ applications were explored, namely, evaluation of their antioxidant activity in the presence of PACs and mDP’s effect in the synthesis of gold nanoparticles. From these experiments it was concluded that, in in vitro cellular assays, PACs’ antioxidant activity could be increased by 45% by combining them with betaine and urea solution in equal mass fractions at a concentration of 2 g/L. Furthermore, it was demonstrated that PACs with high mDP can be utilized in the synthesis of gold-PAC core-shell nanoparticles in which PACs play a simultaneous role of reducing and stabilizing agent.